The Relation of Child’s Empathy and Parents’ Prejudice: The Mediating Role of Parenting Style - Pontania, Almira Rizki; Salim, Rose Mini Agoes (Humaniora, 2019)
This research presented the relationship between a child’s empathy and parents’ prejudice, which was mediated by parenting style. The purpose of this research was to determine whether parenting style could be a mediator between parents’ prejudice and child’s empathy and also what type of parenting style would be appropriate to increase empathy in children. The research respondents consisted of 233 parents who had children aged 6-8 years old and were measured using the Basic Empathy Scale-Parent Report (BES-PR), the Blatant Prejudice Scale, and the Parental Authority Questionnaire-Revised (PAQ-R). The data obtained were processed using Pearson correlation and multiple regression (Hayes process). The results show that parenting style can be a mediator between child’s empathy and parents’ prejudice. The parenting style that can increase empathy in children is authoritative parenting. It means that when parents have a low prejudice, they tend to apply authoritative parenting, and this has an effect on increasing empathy in children.